Skrining Psikologis Counseling Trust Center: Strategi Promotif dan Edukatif Kesehatan Mental Masyarakat - Anasari Anasari; Siti Konaah; Alrefi Alrefi (Program Studi Bimbingan Konseling, Fakultas Tarbiyah dan Ilmu Keguruan UIN Bukittinggi, 2025)
This study aims to provide a comprehensive overview of the psychological condition of the community through a screening program conducted within a community-based service framework. The screening utilized eight instruments measuring psychological flexibility, academic hope, psychological well-being, DASS, test DAMAI, prosocial self-efficacy, multicultural competence, and career interest. A quantitative descriptive method was applied using percentage, frequency, and mean analyses to map respondents’ psychological characteristics. The findings indicate that career planning interest was the most frequently selected domain, reflecting an increasing awareness of the importance of direction and purpose in personal development. In contrast, low participation in prosocial self-efficacy and multicultural competence assessments highlights the need to strengthen social and cultural literacy to support holistic psychological well-being. The results confirm that community-based screening effectively facilitates early detection of psychological conditions while fostering collective awareness of mental health. This study contributes to the development of counseling programs, educator training, and community interventions that promote psychological literacy. Future studies are recommended to employ larger samples and longitudinal measurements to obtain more comprehensive and sustainable insights into community psychological dynamics